The collected poetry - Parker, Dorothy 1893-1967
Brilliant! Dorothy Parker's poetry is ageless. As you read each of the poems in this book, you are taken on a tour, not only of her life but of anyone's "of a certain age." She is wistful, audacious, happy y sad, critical and praising. She "rails against the night" in every way possible and the tour becomes a reflection of your own life in every way. I doubt if Dorothy Parker thought that 60 years later someone else would read her poetry y identify with it. I think she would be pleased!